2023
DOI: 10.1101/2023.07.04.547720
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A cerebellar population coding model for sensorimotor learning

Abstract: The cerebellum plays a critical role in sensorimotor learning, and in particular using error information to keep the sensorimotor system well-calibrated. Here we present a population-coding model of how the cerebellum compensates for motor errors. The model consists of a two-layer network, one corresponding to the cerebellar cortex and the other to the deep cerebellum nuclei, where the units within each layer are tuned to two features, the direction of the movement and the direction of the error. We evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 110 publications
(307 reference statements)
0
2
0
Order By: Relevance
“…For example, when participants are re-exposed to a perturbation after the system has been reset (i.e., a washout phase), implicit adaptation is attenuated [ 40 , 41 ]. We have proposed a neurophysiological-feasible model of the cerebellum in which contextual effects are an emergent property of the population activity of units that embody the rigid properties of the NLMC model [ 42 ]. The aggregate response of the system produces contextual effects due to persistence in the activation of the units, even though the learning parameters of the units themselves remain rigid.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when participants are re-exposed to a perturbation after the system has been reset (i.e., a washout phase), implicit adaptation is attenuated [ 40 , 41 ]. We have proposed a neurophysiological-feasible model of the cerebellum in which contextual effects are an emergent property of the population activity of units that embody the rigid properties of the NLMC model [ 42 ]. The aggregate response of the system produces contextual effects due to persistence in the activation of the units, even though the learning parameters of the units themselves remain rigid.…”
Section: Discussionmentioning
confidence: 99%
“…However, by using methods that isolate the contribution of this recalibration process, we have found that implicit sensorimotor adaptation is actually attenuated during relearning (Avraham et al, 2021; see also Hamel et al, 2022, 2021; Leow et al, 2020; Stark-Inbar et al, 2016; Tsay et al, 2021b; Wang and Ivry, 2023; Yin and Wei, 2020). Savings, when observed in adaptation tasks, appears to largely reflect the operation of other learning processes such as the recall of a successful explicit strategy (Avraham et al, 2021; Haith et al, 2015; Huberdeau et al, 2019; Morehead et al, 2015).…”
Section: Introductionmentioning
confidence: 97%